Penerapan Website Kelurahan Sebagai Media Informasi Kelurahan Jembatan Mas Kecamatan Pemayung Kabupaten Batanghari - Bangsa, Mhd Theo Ari; Alfaizah, Fitria; Sari, Dhevi Permata; Susanti, Eka Desy (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2024)
Digital transformation in the realm of public services has become a necessity in this day and age. The presence of digital technology such as website applications is non-negotiable. Information system websites have an important role in disseminating information and publishing regional potential with a wide reach. Jembatan Mas Village is the only village in Pemayung District, Batanghari Regency. This sub-district does not yet have an information system website. One of the obstacles is the lack of skills and knowledge of sub-district officials in creating and managing websites. Therefore, the community service team created a service activity model in the form of creating and training to manage an information system website in the sub-district. The website was created using the WordPress content management system platform which was customized according to system requirements. The aim of this activity is for the sub-district of Jembatan Mas to have a website that can be managed independently by sub-district officials. Through the sub-district website, all kinds of information about the sub-district can be accessed anywhere and at any time. Apart from that, the potential of the sub-district will be easily publicized and promoted.